Climate Wizard - Zganjar, C; Girvetz, Evan Hartunian; Raber, G (2009)
The Climate Wizard enables technical and non-technical audiences alike to access leading climate change information and visualize the impacts anywhere on Earth. • With Climate Wizard users can: view historic temperature and rainfall maps, view state-of-the-art future predictions of temperature and rainfall, and view and download climate change maps in a few easy steps. • The website is designed to be integrated within the government or other institutional websites to provide a seamless look and user experience.